Increase in Oxidation Resistance of MAR M-509 via LA-CVD Aluminizing - Wojciech J. Nowak (MDPI AG, 2021)
Due to their excellent mechanical properties, Co-based alloys are one of the main candidates to replace Ni-based alloys in high temperature application. Knowledge about oxidation resistance of Co-based alloy MAR M-509 and the extent of its aluminizing on its oxidation resistance is limited. Therefore, in the present study, an aluminide layer was manufactured by low activity chemical vapor deposition (LA-CVD) on MAR M-509. Aluminized and uncoated alloys were investigated in terms of oxidation kinetics and oxidation resistance during isothermal and cyclic oxidation at 1000 and 1100 °C. Material in the as-cast and after exposure was analyzed using scanning electron microscopy (SEM), thermogravimetry (TG) and glow-discharge optical emission spectrometry (GD-OES). Obtained results allowed for elucidating of degradation mechanism including nitridation process of carbides for MAR M-509. It was found that aluminizing of MAR M-509 significantly decreases its oxidation kinetics by the factor of 2.5 and 1.5 at 1000 and 1100 °C respectively. Moreover, the suppression of identified degradation mechanism in case of aluminized alloy was found until occurrence of breakaway oxidation of the aluminide layer. It was also proposed that further increase in oxidation resistance can be successively achieved by an increase in aluminide layer thickness.